2011
DOI: 10.1002/jcc.21891
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different potentials on the structures and energies of clusters

Abstract: Cluster studies have attracted much interest in the past decades because of their extraordinary properties. To describe the interaction between atoms or molecules and predict the energies and structures, potential functions are developed. However, different potentials generally produce different structures and energies for a cluster. To study the effect of potentials on the structure of a cluster, He clusters in the size range of 13-140 are investigated by Lennard-Jones (LJ), Pirani, and Hartree-Fock-dispersio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…8 Furthermore, the impact of LJ, Pirani, and Hartree−Fock-dispersion individual damping (HFD-ID) potentials on the structure, bond length, and energy was investigated. 17 It was found that although the three potentials were very similar near well depth, there existed differences at long and short ranges, and the number of the bonds that deviated from 1.00 might be the dominant factor determining the structure of a cluster. Moreover, for N-atom binary A l B m (l + m = N) LJ clusters, the stabilization of polytetrahedral structures 18 was studied by structural phase diagram depending on atomic size N and the ratio parameter (σ BB /σ AA ) of pure elemental B-and A-type LJ cluster sizes, and it was concluded that different structures, particularly those that are polytetrahedral, can be stabilized just through the two atom types in the cluster having different sizes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…8 Furthermore, the impact of LJ, Pirani, and Hartree−Fock-dispersion individual damping (HFD-ID) potentials on the structure, bond length, and energy was investigated. 17 It was found that although the three potentials were very similar near well depth, there existed differences at long and short ranges, and the number of the bonds that deviated from 1.00 might be the dominant factor determining the structure of a cluster. Moreover, for N-atom binary A l B m (l + m = N) LJ clusters, the stabilization of polytetrahedral structures 18 was studied by structural phase diagram depending on atomic size N and the ratio parameter (σ BB /σ AA ) of pure elemental B-and A-type LJ cluster sizes, and it was concluded that different structures, particularly those that are polytetrahedral, can be stabilized just through the two atom types in the cluster having different sizes.…”
Section: Introductionmentioning
confidence: 97%
“…To investigate the strongly mixed rare gas clusters, various systems from binary to quinary mixtures of atom types were systematically analyzed by using LJ potentials fitting to high-end ab initio reference data . Furthermore, the impact of LJ, Pirani, and Hartree–Fock-dispersion individual damping (HFD-ID) potentials on the structure, bond length, and energy was investigated . It was found that although the three potentials were very similar near well depth, there existed differences at long and short ranges, and the number of the bonds that deviated from 1.00 might be the dominant factor determining the structure of a cluster.…”
Section: Introductionmentioning
confidence: 99%